Publishing Ecological Data in a Repository: An Easy Workflow for Everyone. Issue 4 (10th August 2022) - Vanderbilt, Kristin; Ide, Jon; Gries, Corinna; Grossman‐Clarke, Susanne; Hanson, Paul; O'Brien, Margaret; Servilla, Mark; Smith, Colin; Waide, Robert; Zollo‐Venecek, Kyle
Abstract: For many ecologists, publishing data in a data repository is a new, unfamiliar task. To reduce the learning curve, the Environmental Data Initiative has developed user‐friendly software to make capturing and submitting data and metadata a simple process. In this article, we introduce ezEML and discuss use cases for researchers who publish data infrequently or information managers who regularly update multiple datasets.